Allele Frequencies and Forensic Statistical Parameters for 21 Autosomal Short Tandem Repeats (STRs) loci in Northern Thai Population - Supakit Khacha-ananda; Yutti Amornlertwatana; Phatcharin Mahawong; Nitaya Khamkomkai (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Although the genetic information of STRs has been established over the entire world, the differentcharacteristics between populations influenced the STRs information. FBI’s guideline recommended to expandadditional number of STRs loci to increase power of discrimination and exclusion. Unfortunately, the currentdata of STRs in northern Thai population have not fully covered additional loci. The aim of this study is to obtainaccurate allele frequencies of STRs among northern Thai population.Methods: The genetic profiles ofunrelated individuals were characterized by Investigator 24 plex Go kit. Allelefrequencies and forensic statistical parameters were calculated within GenoProof®3and Arlequin ver 3.5.2.2.Results: The SE33 and TH01 loci represented largest and lowest number of different alleles, respectively. Therewas no significant deviation from the Hardy–Weinberg equilibrium (HWE) after Bonferroni correction in all loci(p=0.002). The SE33 locus showed the greatest PD and PE, whereas the TPOX represented the lowest PD and PE.The studied population (northern Thai) appear to be most closely related to previously reported populationscontaining of Chinese, Japanese, and Vietnamese based on allele frequency.Conclusion: Our results recommended that current autosomal STRs data extended the application of STRs typingin parentage analyses and human identification among the localized population in northern region of Thailanddue to highly informative polymorphic data.